Selection of topical corticosteroids in children atopic dermatitis - Aurelia Stephanie; Prima Sanjiwani Saraswati Sudarsa; Luh Mas Rusyati (Bali Dermatology and Venereology Journal, 2019)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disease that typically starts in childhood with classic symptoms of dry and itchy skin that occurs continuously and recurrences and even causes sleep disorders and skin that is susceptible to infection. AD sufferers often have atopic comorbidities such as asthma and allergic rhinitis in themselves and their families. The effects of this itching cycle result in growth disturbance and decreased quality of life for AD patients and their parents. Moderate and severe AD have an impact on parents, the stress in medication, and care, which takes up time and money. Atopic dermatitis is due to damage to the skin barrier, so the principle of management is to improve the skin barrier so that the inflammatory process can be avoided. The course of AD is chronic and relapsing; generally, patients come for treatment with an acute phase that sometimes requires topical corticosteroids. However, topical corticosteroids (TC) are used only to treat the acute phase for a short period. After the acute lesions have subsided, corticosteroids can be stopped immediately to prevent side effects and continue with daily skincare.Conclusion: Topical corticosteroids are first-line therapy in the acute phase. The choice of TC is based on age, body location, dosage, and severity of AD. If the acute lesion has subsided, then corticosteroids can be stopped and substituted with other antipruritic therapy and moisturizer.